2017
DOI: 10.1159/000477432
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Cerebellar and Neocortical Expansion in Anthropoid Primates: A Comparative Approach

Abstract: What adaptive changes in brain structure and function underpin the evolution of increased cognitive performance in humans and our close relatives? Identifying the genetic basis of brain evolution has become a major tool in answering this question. Numerous cases of positive selection, altered gene expression or gene duplication have been identified that may contribute to the evolution of the neocortex, which is widely assumed to play a predominant role in cognitive evolution. However, the components of the neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 102 publications
5
19
0
Order By: Relevance
“…Our results are therefore consistent with a “mosaic” model of brain evolution (Barton & Harvey, ), and data from molecular studies in other vertebrates that suggest selection may act on independent sets of genes and developmental pathways that control the size of each brain component (e.g. Noreikiene et al, ; Harrison & Montgomery, ; Montgomery et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…Our results are therefore consistent with a “mosaic” model of brain evolution (Barton & Harvey, ), and data from molecular studies in other vertebrates that suggest selection may act on independent sets of genes and developmental pathways that control the size of each brain component (e.g. Noreikiene et al, ; Harrison & Montgomery, ; Montgomery et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…However, the brain is composed of functionally and anatomically heterogeneous structures which show heterochronicity in their development (5)(6)(7)(8). It has also been demonstrated that structures' developmental scheduling is influenced by structure-specific genes (12). It is therefore possible that different brain structures have different life history correlates.…”
mentioning
confidence: 99%
“…This region is even larger in apes relative to monkeys [Rilling and Insel, 1998], which may reflect increased technical intelligence related to the complex tool use abilities observed in great apes [Barton and Venditti, 2014]. In fact, the cerebellum underwent rapid evolutionary expansion during ape evolution [Barton and Venditti, 2014;Smaers et al, 2018;Miller et al, 2019], and genes involved in cerebellum development are more likely to have evolved adaptively during hominoid evolution than those involved in cortical development [Harrison and Montgomery, 2017]. Thus far, sex differences in the relative cerebellum size have only been investigated in humans, with studies showing mixed results [e.g., female-biased: Hutchinson et al, 2003; male-biased: Raz et al, 1998Raz et al, , 2001; no difference: Filipek et al, 1994;Luft et al, 1998, Nopoulos et al, 2000Szabó et al, 2003;Leonard et al, 2008;Fan et al, 2010].…”
Section: Introductionmentioning
confidence: 99%